The Impact of Supportive Leadership on Work Stress: An Empirical Research in the Ministry of Iraqi Interior - Adil Ibrahim al-Gburi *, Hussein; Rashed Musaheb, Mohsin (Journal of Economics and Administrative Sciences, 2024)
Purpose: The purpose of this research is to discover the effect of supportive leadership on work stress in the Ministry of Iraqi Interior / Human Resources Management to achieve a happy life for its employees and hence achieve the desired level of performance.Theoretical Framework: The current research deals with introducing the Ministry of Iraqi Interior / Human Resources Management to the latest developments in the administration field through supportive leadership style and work stress, as well as presenting the latest concepts, importance, and models that previous researchers have arrived at. It contributes to expanding the researched organization's awareness of adopting any of these models that are appropriate for their goals and future direction.Design/Methodology/Approach: The research analyses administrative data within the Ministry of Iraqi Interior / Human Resources Management (2023-2024), using the dimensions of supportive leadership (empowering employees, fairness of treatment, and inspirational motivation) and the dimensions of work stress (role ambiguity, role conflict, workload, and work nature). It will determine the factors affecting them.Findings: The findings of this current research have approved the key effect hypothesis (supportive leadership style and its dimensions have a significant and negative impact on work stress and its dimensions).Research Implications: The results most leaders of human resources in the under-study organization practice the dimension of fair treatment more than other dimensions (empowering employees, and inspirational motivation.Originality/Value: This research seeks to enhance awareness of the importance of the negative role of a supportive leadership style on work stress. This research has dropped the knowledge gap between them and uses a framework that is compatible and harmonious to save the lives of the employees and at the same time increase organizational performance.